Rheumatoid meningitis: A case report and review of the literature - Qin, Zhaoyi (Neurol Clin Pract, 2020)
PURPOSE OF REVIEW: Rheumatoid arthritis is a systemic inflammatory disorder, which can involve many organs; among which, CNS involvement, as in rheumatoid meningitis (RM), is rare and difficult to recognize. Our goal is to present collective data of RM cases to better characterize this disease process and to start new discussions about pathophysiology, diagnosis, and treatment. RECENT FINDINGS: Since Kato et al., 39 cases of RM have been reported. Approximately 59% were women, presenting with neurologic deficits (56%) and diagnosed by MRI findings, leptomeningeal enhancement (69%), after CSF analysis. Seventy-four percent were treated with corticosteroids, 64% as maintenance therapy, with 46% experiencing improvement or resolution in symptoms without relapse. SUMMARY: Diagnosis and prognosis of RM has drastically changed since the year 2000. Early detection with CSF and MRI or biopsy findings, coupled with early treatment using corticosteroids and immunologic therapy, has reduced mortality in this population.